Orthodox Christian material culture of people and things in the making of heaven - Carroll, Timothy (Routledge studies in anthropology, 2018)
"Although much has been written on the making of art objects as a means of engaging in creative productions of the self (most famously Alfred Gells work), there has been very little written on Orthodox Christianity and its use of material within religious self-formation. Eastern Orthodox Christianity is renowned for its artistry and the aesthetics of its worship being an integral part of devout practice. Yet this is an area with little ethnographic exploration available and even scarcer ethnographic attention given to the material culture of Eastern Christianity outside the traditional homelands of the greater Levant and Eastern Europe. Drawing from and building upon Gells work, Carroll explores the uses and purposes of material culture in Eastern Orthodox Christian worshipages Drawing on three years of ethnographic fieldwork in a small Antiochian Orthodox parish in London, Carroll focusses on a study of ecclesiastical fabric but places this within the wider context of Orthodox material ecology in Britain. This ethnographic exploration leads to discussion on the role of materials in the construction of religious identity, material understandings of religion, and pathways of pilgrimatic engagement and religious movement across Europe. In a religious tradition characterised by repetition and continuity, but also as sensuously tactile, this book argues that material objects are necessary for the continual production of Orthodox Christians as art-like subjects. It is an important contribution to the corpus of literature on the anthropology of material culture and art and the anthropology of religion."--Provided by publisher